Effect of nursing home ownership on hospitalization of long-stay residents: an instrumental variables approach - Hirth, Richard A. (2014)
Hospitalizations among nursing home residents are frequent, expensive, and often associated with further deterioration of resident condition. The literature indicates that a substantial fraction of admissions is potentially preventable and that nonprofit nursing homes are less likely to hospitalize their residents. However, the correlation between ownership and hospitalization might reflect unobserved resident differences rather than a causal relationship. Using national minimum data set assessments linked with Medicare claims, we use a national cohort of long-stay residents who were newly admitted to nursing homes within an 18-month period spanning January 1, 2004 and June 30, 2005. After instrumenting for ownership status, we found that IV estimates of the effect of nonprofit ownership on hospitalization are at least as large as the non-instrumented effects, indicating that selection bias does not explain the observed relationship. We also found evidence suggesting the lower rate of hospitalizations among nonprofits was due to a different threshold for transfer.